The CIA and the Congress for Cultural Freedom in the Early Cold War the limits of making common cause - Harris, Sarah Miller (Studies in intelligence, 2016)
This book questions the conventional wisdom about one of the most controversial episodes in the Cold War, and tells the story of the CIA's backing of the Congress for Cultural Freedom. Using a wealth of archival research and interviews with many of the figures associated with the Congress, this book sheds new light on how the Congress came into existence and functioned, both as a magnet for prominent intellectuals and as a CIA operation.